Single sport specialization in the skeletally immature athlete. Current concepts - Lansdown, D. A.; Rugg, C. M.; Feeley, B. T.; Pandya, N. K. (Journal of the American Academy of Orthopaedic Surgeons, 2020)
Youth sport participation patterns have drastically changed over the past two decades. Increasingly, young individuals are specializing in single sport while skeletally immature. Sport specialization in the growing athlete has profound effects on performance, short- and long-term injury risks, and joint health. Evidence continues to mount as the detrimental effects of this trend on the immature athlete. The knee, shoulder, and elbow of these young athletes are particularly affected by this emphasis on skill-based sporting activity as opposed to generalized fitness and participation. An understanding of the epidemiology of sport participation, particularly financial impacts, and the effects on elite sport performance are critical so that the clinician can effectively educate athletes, parents, and coaches.